Licenced to transplant: UK overkill on EU Organ Directive provides golden opportunity for research. Issue 10 (8th August 2012) - Cronin, Antonia J; Douglas, James; Sacks, Steven
Abstract : Progress in transplantation outcomes depends on continuing research into both donor and recipient factors that may enhance graft and patient survival. A system of licencing for transplantation research, introduced by the Human Tissue Act 2004, which separates it from the transplantation process (then exempt from licencing), has damaged this vital activity by a combination of inflexible interpretation of the 2004 Act and fear of criminal liability on the part of researchers. Now, following the European Union (EU) Directive (2010) on standards of quality and safety of human organs intended for transplantation, new UK Regulations have been drafted, which are intended to implement it. These Regulations impose a compulsory licencing system, similar to that for research, on the whole transplantation process. This goes beyond what is required by the Directive and may even have an inhibitory effect similar to that already seen in research. Initial draft Regulations went further, imposing criminal sanctions for breaches. However, following a public consultation process, the Department of Health (DH) has recently stated that, as a result of the overwhelming view of respondents that the proposed licencing system was unnecessary, all sanctions under the final Regulations are now decriminalised, with the sole exception of operating without a licence. While this does not eliminate the negative effect of licencing, it does suggest an awareness of the DH that excessive regulation unnecessarily harms the transplantation process. An opportunity thus arises for the Human Tissue Authority (the regulatory body for both the new licences and research licences under the 2004 Act) to end the current illogical and harmful separation of transplantation and transplantation research by ensuring that all centres licenced for organ donation, retrieval and transplantation are also fully licenced for related research.